Evaluation of Rural Community Adaptation and Mitigation to Climate Change Using a Discrete Choice Experiment - Komarudin, Nurul Amri; Fahrunnisa, Fahrunnisa; Afgani, Chairul Anam (Jurnal Agroekoteknologi Terapan, 2025)
The agricultural sector is one of the most vulnerable to the impacts of climate change, necessitating adaptation and mitigation strategies to safeguard farmers’ livelihoods, which heavily rely on natural conditions and climate factors. This study aims to evaluate the knowledge and perceptions of farming households regarding the impacts of climate change in the agricultural sector using a Discrete Choice Experiment (DCE). The study was conducted in Batu Dulang Village, Batulanteh Subdistrict, Sumbawa Regency. The approach utilized both quantitative and qualitative methods. Quantitative data were collected through a survey of 100 farming households, while qualitative data were obtained through in-depth interviews. The DCE method was employed to determine farmers’ preferences for selecting the most suitable adaptation and mitigation strategies. The study results indicate that the preferred attributes of climate change adaptation and mitigation activities of rural communities from the most preferred are forest conservation schemes through agroforestry systems, followed by emission reduction, increased food security, natural disaster control, and waste management. Attributes with greater direct utility for respondents, such as forest conservation and emission reduction, have higher marginal utility coefficients than others. Individuals are willing to pay for preferred attributes, indicating that climate conditions are an integral part of their livelihoods because the agricultural sector is highly dependent on climate and natural conditions. Keywords: adaptation, climate change, discrete choice experiment, farmer preferences, mitigation